Use of Steroid-Eluting Stents after Endoscopic Repair of Choanal Atresia: A Case Series with Review. (October 2020) - Wilcox, Lyndy J.; Smith, Matthew M.; de Alarcon, Alessandro; Epperson, Madison; Born, Hayley; Hart, Catherine K.
Objective(s): To describe a single institution's experience with the use of steroid-eluting stents after endoscopic transnasal repair of choanal atresia. Methods: A case series with review of children who underwent choanal atresia repair at a tertiary children's hospital from June 2017 to January 2018 was performed. Those who had a mometasone drug-eluting stent (Propel ® Mini, Intersect ENT Inc., Palo Alto, CA) placed after primary or secondary choanal atresia repair at our institution were included. The primary outcome measure was need for revision surgery due to stenosis. Postoperative regimens, duration of stenting, and need for return to the operating room (OR) were also assessed. Results: Five patients with a median age of 22 months at the time of repair met inclusion criteria. Two (40%) had bilateral atresia and 3 (60%) had confirmed CHARGE syndrome. A total of 6 mometasone drug-eluting stents were used in the 5 cases. Three patients were reassessed at least once in the OR; however, the majority (57.1%) of postoperative evaluations were able to be performed in the office or bedside setting. The first and last evaluations occurred a mean of 14 and 124 days after surgery, respectively. There were no instances of restenosis, repeat surgical interventions, or stent-related complications noted. Conclusion: Placement of a mometasone drug-eluting stent is a promising method to improve postoperative results and management of choanal atresia repair by limiting the need for repeat anesthetics and OR procedures, as well as the complications of traditional stents.